The Effect of Mnemonic Method with a Deductive Approach in Shorof Learning on Students Learning Outcomes - Sholiha, Amila; Rofiqi, Muhammad; Muhajir, Muhajir; Sidik, Firdan Fadlan (Arabiyatuna: Jurnal Bahasa Arab, 2023)
The aim of this research is to see how using a mnemonic method with a deductive approach affects in shorof learning outcomes of Interdisciplinary Islamic Studies students at Nahdhatul Ulama University Yogyakarta. Success in learning can be influenced by the selection of appropriate methods by the teacher during learning. One of the methods that can be used is the mnemonic method. This quantitative research used an experimental technique, a quasi-one-group pretest-posttest design. The acquired data were evaluated using descriptive statistical tests, a normality test with Kolmogorov-Smirnov, and a paired sample t-test. The findings of this research demonstrated that using the rhyme mnemonic method with a deductive approach to the subject of isim jamid in shorof learning, paired with the rhyme of sholawat badar, had an effect on students' learning outcomes. This was shown by an increase in the average students’ pretest score from 61.50 to the average students’ posttest score of 81.67. The results of the significant value of the paired sample t-test being 0.000 also reinforced this effect. These significant findings revealed that Sig 0.000 < 0.05, indicating a substantial difference in students’ learning outcomes before and after using the mnemonic method with a deductive approach in shorof learning. Suggestions for further research are to vary learning methods and approaches, considering that this way can affect the level of students’ understanding of the materials taught.